Indonesian Spelling Errors in the Description Text - Harzoni Harzoni; Suhirman Suhirman; Ixsir Eliya (Yayasan Karinosseff Muda Indonesia, 2022)
The purpose of this study was to describe the form of spelling errors in the descriptive text of class VII A students of SMP Negeri 05 Bengkulu City. This study uses a qualitative research type with a descriptive approach. Based on the discussion of research data on the analysis kesalaha n spelling of Indonesian in the essay on pembelaja ran B ahasa Indonesian students of class VII A Junior High School 05 Bengkulu city, the writer can give the conclusion that in general the students of class VII A SMPN 05 Kota Bengkulu have not mastered the use of letters, word writing, the use of punctuation in writing essays. Classically, students have not been able to understand the general use of Indonesian spelling (PUEBI)in writing an essay. Because students still have difficulty in understanding the use of Indonesian spelling. The results of the study concluded that letter errors, writing errors, punctuation errors, from the data that the authors found there were errors in the use of capital letters and italics, words with affixes, errors in writing abbreviations and acronyms, periods, commas, colons, hyphens. , dash. As for errors in the use of letters of the alphabet, vowels, consonants, diphthongs, combinations of consonants and bold letters, basic words, repeated forms, word combinations, word decapitation, particles, numbers and numbers, pronouns, articles, slashes, question marks, exclamation marks, ellipsis marks, quotation marks, single quotation marks, brackets, square marks, and abbreviations were not found errors from the research data.